2018
DOI: 10.1002/jbm.a.36336
|View full text |Cite
|
Sign up to set email alerts
|

Composite porous scaffold of PEG/PLA support improved bone matrix deposition in vitro compared to PLA‐only scaffolds

Abstract: Controllable pore size and architecture are essential properties for tissue-engineering scaffolds to support cell ingrowth colonization. To investigate the effect of polyethylene glycol (PEG) addition on porosity and bone-cell behavior, porous polylactic acid (PLA)-PEG scaffolds were developed with varied weight ratios of PLA-PEG (100/0, 90/10, 75/25) using solvent casting and porogen leaching. Sugar 200-300 µm in size was used as a porogen. To assess scaffold suitability for bone tissue engineering, MLO-A5 mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 30 publications
2
38
0
2
Order By: Relevance
“…As MLO-A5s cultured in supplemented media, they were expected to deposit calcified extracellular matrix (ECM) [47,72,73]. Prideaux et al previously reported that supplementation of MLO-A5 cell cultures with AA2P and βGP showed a significant increase in ECM mineralization compared to the non-supplemented group [14].…”
Section: Resultsmentioning
confidence: 99%
“…As MLO-A5s cultured in supplemented media, they were expected to deposit calcified extracellular matrix (ECM) [47,72,73]. Prideaux et al previously reported that supplementation of MLO-A5 cell cultures with AA2P and βGP showed a significant increase in ECM mineralization compared to the non-supplemented group [14].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, composites of ceramic and biodegradable metal such as magnesium-calcium phosphate can provide superior biocompatibility, biodegradability and faster and more efficient osteogenesis in vivo [101]. Polymer-polymer composites have also been extensively developed for making bone scaffolds with better function, examples are scaffolds made of polyethylene glycol (PEG)-PLA [102], PLA-polyaniline (PANI) [103], chitosan-collagen-hyaluronic acid [104] and many others. It should be pointed out despite the advantages offered by uniform composite, there is a trade-off between the material properties.…”
Section: Advanced Materialsmentioning
confidence: 99%
“…PLLA scaffolds with the application in bone tissue engineering could be prepared by FDM [32], also with the additives as hydroxyapatite [33] or with collagen after further modification [34]. Other methods of the preparation include electrospinning for PLA scaffolds with hydroxyapatite and collagen [35] or porogen leaching for the scaffolds made of PLA blends with polyethylene glycol [36]. Amorphous poly(trimethylene carbonate) (PTMC) has only limited applications comparing with the other biodegradable polymers [37].…”
Section: Introductionmentioning
confidence: 99%